Kemuliaan Allah sebagai Tujuan Penciptaan dalam Katekismus Gereja Katolik Artikel 293 - Wiguna, Vincentius Agsuko (Felicitas, 2021)
This paper is entitled "The Glory of God as the End of Creation". The starting point of this paper was begun from a reading of the Catechism of the Catholic Church art. 293. In general, the author took this theme to contemplate one of the subjects related to Creation. In particular, the author wanted to explore and reflect on the glory of God. In this case, the meaning of "the glory of God" would be examined from the etymological, biblical side, and see its relationship in the celebration of the Church's Liturgy, namely the Eucharist and Divine Office. At the end, the writer related it to the end of Creation.